Protein cage assisted metal-protein nanocomposite synthesis : optimization of loading conditions - Sana, Barindra (2013)
Ferritin is an iron-storage protein in most living systems with a cage-like structure. It has inherent property to form metallic nanocore within its cavity. The metallic core formed within the Archaeoglobus fulgidus ferritin cavity is stabilized by modulating the protein structure by site directed mutagenesis. Encapsulation protocol of various metals within the engineered ferritin cage (AfFtn-AA) is optimized. Dense metallic cores are visualized using electron microscopy and the bound metal was quantified by ICP-spectrometry. The AfFtn-AA is loaded with up to about 350 cobalt, 2000 chromium, and as high as 7000 iron atoms, separately. The metal-protein nanocomposites formed by encapsulation of cobalt, chromium, and iron are studied. Magnetic resonance imaging of the agarose embedded nanocomposites shows brightening of T1-weighted images and signal loss of T2-weighted images with increasing concentration of the nanocomposites. Shortening of magnetic relaxation times in the presence of the nanocomposites confirm their ability to enhance magnetic relaxation rate and suggests that the nanocomposites have potential application as MRI contrast agent.